Pengaruh Faktor Lingkungan Terhadap Keputusan Pembelian Jamu Tradisional: Peran Inovasi Produk dan Kreativitas Strategi Pemasaran Sebagai Variabel Moderating - Aenul Ma’rifah; Dumadi Dumadi; Syarieful Ikhwan (Al-Buhuts, 2025)
This study aims to analyze the influence of environmental factors on purchasing decisions of traditional herbal medicine, with product innovation and marketing strategy creativity as moderating variables. The method used is a survey with a quantitative approach. The results of the study indicate that environmental factors do not have a direct effect on purchasing decisions, but have an effect on product innovation and marketing strategy creativity, which is proven to moderate the relationship between environmental factors and purchasing decisions, while product innovation does not have a significant role in this moderation.